Settlement analysis of the large-dimensional shallow foundations founded on sand - Rakić Dragoslav; Milosavljević Marija; Đurić Tina; Matić Anđelko; Ljubojev Milenko (Mining and Metallurgy Engineering Bor, 2025)
In practice, a number of methods have been developed for calculating the settlement of shallow foundations on sand, but in general it can be said that there is no standardized calculation method. The practice has shown that when calculating the settlement of mat foundation of large dimensions, significantly larger settlements are obtained compared to the measured ones. This may indicate certain shortcomings when using the usual empirical relations for settlement calculation. This work presents the most commonly used semi-empirical methods for calculating the foundation settlement on sandy soils, and it analyzes the results obtained using different approaches (Schmertmann et al., 1970, 1978; Schultze and Sherif, 1973; Janbu et al., 1956), including the numerical simulations in the Settle3 program, which combines the simplicity of one-dimensional settlement analysis with the visualization capabilities of more modern three-dimensional programs. The analysis was carried out on one specific facility that was built in Novi Sad. During its construction, geodetic monitoring of settlement was performed, which enabled a comparison between the calculated and measured values.